1997
DOI: 10.1002/hep.510250326
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibition by enalapril: A novel approach to reduce ischemia/reperfusion damage after experimental liver transplantation

Abstract: emia/reperfusion injury in clinical liver transplantaAngiotensin-converting enzyme (ACE) inhibitors tion. (HEPATOLOGY 1997; 25:648-651.) have proven to be effective in the reduction of ischemia/reperfusion damage after myocardial ischemia. Whether this favorable effect can be related to other models of ischemia and reperfusion has not After more than 20 years of clinical experience, liver transyet been investigated. Therefore, we studied in a plantation is an established treatment modality for end-stage model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 9 publications
1
27
0
1
Order By: Relevance
“…Because ACEIs increase the level of bradykinin, our findings emphasize the importance of using ACEIs in situations in which I/R injury is likely to occur. Pretransplant treatment of the donor with ACEIs, as well as posttransplant treatment of the recipient, merits consideration (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ACEIs increase the level of bradykinin, our findings emphasize the importance of using ACEIs in situations in which I/R injury is likely to occur. Pretransplant treatment of the donor with ACEIs, as well as posttransplant treatment of the recipient, merits consideration (5).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-I-converting enzyme (ACE) inhibitors (ACEIs) reduce not only chronic cardiovascular remodeling after ischemia but also acute tissue injury caused by I/R in the heart (3), lung (4), liver (5), and kidneys (6,7). Several observations indicate that the beneficial effects of ACEIs in the acute phase are mainly due to activation of the bradykinin nitric oxide (NO) cascade as a result of inhibition of the inactivation of bradykinin, rather than due to suppression of angiotensin II formation.…”
mentioning
confidence: 99%
“…It is well established that ACE inhibitors prevent not only chronic cardiovascular remodeling after ischemia but also acute tissue injury caused by ischemia/reperfusion in the heart, lung, liver and kidneys (23)(24)(25)(26)(27). Interestingly, it has been demonstrated that the beneficial effects of ACE inhibitors in the acute phase are mainly due to the activation of bradykinin-NO or of the bradykinin-prostacyclin cascade, rather than to the suppression of angiotensin II, because angiotensin type 1 receptor antagonists have been clearly shown to be less beneficial than ACE inhibitors in previous studies (28,29), and because addition of bradykinin type 2 receptor antagonists has been shown to abolish the effects of ACE inhibitors (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, Ang II causes vascular injury and organ damage. In fact, several lines of evidence have implicated that inhibition of Ang II may protect against ischemia-reperfusion-induced tissue injury in the heart, brain, liver, kidney, and small intestine (1,5,17,42). Previous studies have shown that the increase in Ang II is more prominent in the splanchnic circulation than in the systemic circulation during major aortic surgery and hypovolemia (44).…”
Section: Discussionmentioning
confidence: 99%